2010
DOI: 10.1093/jxb/erq229
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting phytochemicals for developing a 'push-pull' crop protection strategy for cereal farmers in Africa

Abstract: Lepidopteran stemborers and parasitic weeds in the genus Striga are major constraints to efficient production of cereals, the most important staple food crops in Africa. Smallholder farmers are resource constrained and unable to afford expensive chemicals for crop protection. Development of a push-pull approach for integrated pest and weed management is reviewed here. Appropriate plants were discovered that naturally emit signalling chemicals (semiochemicals). Plants highly attractive for egg laying by stembor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
151
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(160 citation statements)
references
References 61 publications
1
151
0
2
Order By: Relevance
“…The push-pull strategy, also referred to as stimulo-deterrent diversionary strategy, entails the control of pests by repelling them from the main crop (push) using stimuli that masks a host or is repellent or a deterrent while simultaneously attracting (pull) the pest, using highly attractive stimuli, to other areas such as traps or trap crops where they are concentrated and eventually eliminated (Cook, Khan, & Pickett, 2006;Miller & Cowles, 1990). Recent studies have reported successful control of lepidopteran stem borers on maize crop in Kenya, by employing crop mixtures in push-pull strategies (Hassanali et al, 2008), a technique so far adopted by more than 30,000 farmers across East Africa (Khan, Midega, Bruce, Hooper, & Pickett, 2010).…”
Section: Pest and Disease Controlmentioning
confidence: 99%
“…The push-pull strategy, also referred to as stimulo-deterrent diversionary strategy, entails the control of pests by repelling them from the main crop (push) using stimuli that masks a host or is repellent or a deterrent while simultaneously attracting (pull) the pest, using highly attractive stimuli, to other areas such as traps or trap crops where they are concentrated and eventually eliminated (Cook, Khan, & Pickett, 2006;Miller & Cowles, 1990). Recent studies have reported successful control of lepidopteran stem borers on maize crop in Kenya, by employing crop mixtures in push-pull strategies (Hassanali et al, 2008), a technique so far adopted by more than 30,000 farmers across East Africa (Khan, Midega, Bruce, Hooper, & Pickett, 2010).…”
Section: Pest and Disease Controlmentioning
confidence: 99%
“…This represents a sophisticated defence response which provides timely and effective biological control early on, before much damage is caused by the hatching larvae [11,28]. Some plant species constitutively release volatile semiochemicals that repel insect pests and attract natural enemies of the herbivore [29,30]. More examples on ecological functions of plant-derived volatile semiochemicals have been well documented [9,23,31,32].…”
Section: Role Of Induced and Constitutive Volatiles In Plant Defencementioning
confidence: 99%
“…One of the most successful examples of a stimulo-deterrent diversionary strategy is a 'push-pull' cropping system developed to control cereal stemborers for resource-poor farmers in Africa [30]. The system involves intercropping cereal crops maize or sorghum, with the fodder legumes desmodium spp.…”
Section: Stimulo-deterrent Diversionary Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…This practice, the 'push-pull system', has been carefully studied in maize and bean crops, in Africa. Well-designed, replicated trials have demonstrated positive effects on natural enemies, reduced pest number, pest damage and increased yields in response to this practice (for example, Khan et al 2010; see http://www.conservationevidence.com/actions/ 753, or Wright et al (2013) for links to all 10 relevant studies). It clearly has strong potential to enhance natural pest regulation.…”
Section: Evidence Assessment For Selected Practicesmentioning
confidence: 99%